Viability of Islamic Insurance (Takaful) in India: SWOT analysis approach - Htay, Sheila Nu Nu; Syed, Ahmed Salman (Canadian Center of Science and Education, 2013)
Takaful (Islamic insurance) has been widely accepted as an alternative to conventional insurance and offered in many Muslim and non-Muslim countries. The unique feature of Takaful is that is suitable and acceptable for anyone regardless of the religion to our surprise, Takaful has not been introduced in India. India has the third largest Muslim population after Indonesia and Pakistan and second largest population after China. In terms of economic development, India’s GDP growth rate is 6.3% and it is expected that in coming years and it is believed that India will be one of the leading countries for the world economy. Thus, the objective is to examine the viability of Takaful in India by using SWOT analysis approach. Questionnaire has been distributed to both Muslim and non-Muslims to find out the awareness, acceptability, prospects and challenges of Takaful products. Interviews have been conducted to examine the opinions of ten insurance operators, fifteen Shari’ah advisors and five consultants regarding the prospects and challenges of introducing Takaful in India. The findings from 333 respondents show that awareness of Takaful is still at the minimum level. However, they are willing to participate if Takaful is offered in India. In addition, the findings of the interviews highlight that the Takaful has a good potential in India. However, it can be offered if the government supports it. Due to time limitation, the opinion of the regulators has not been examined and thus, future research should focus on it.